2018
DOI: 10.1186/s12938-018-0539-8
|View full text |Cite
|
Sign up to set email alerts
|

PCA and deep learning based myoelectric grasping control of a prosthetic hand

Abstract: BackgroundFor the functional control of prosthetic hand, it is insufficient to obtain only the motion pattern information. As far as practicality is concerned, the control of the prosthetic hand force is indispensable. The application value of prosthetic hand will be greatly improved if the stable grip of prosthetic hand can be achieved. To address this problem, in this study, a bio-signal control method for grasping control of a prosthetic hand is proposed to improve patient’s sense of using prosthetic hand a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 17 publications
0
33
0
4
Order By: Relevance
“…Hand motion recognition [9][10][11][12][13][14][15][16][17], Muscle activity recognition [18][19][20][21][22][23] ECG Heartbeat signal classification , Heart disease classification [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63], Sleep-stage classification [64][65][66][67][68], Emotion classification [69], age and gender prediction [70] EEG Brain functionality classification , Brain disease classification , Emotion classification [122][123][124][125][126][127][128][129], Sleep-stage classification [130][131][132][133]…”
Section: Emgmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand motion recognition [9][10][11][12][13][14][15][16][17], Muscle activity recognition [18][19][20][21][22][23] ECG Heartbeat signal classification , Heart disease classification [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63], Sleep-stage classification [64][65][66][67][68], Emotion classification [69], age and gender prediction [70] EEG Brain functionality classification , Brain disease classification , Emotion classification [122][123][124][125][126][127][128][129], Sleep-stage classification [130][131][132][133]…”
Section: Emgmentioning
confidence: 99%
“…For the hand-grasping classification described by Li et al [14], principal component analysis (PCA) method is used for dimension reduction and DNN with a stack of 2-layered auto-encoders, and a SoftMax classifier is applied for classifying levels of force.…”
Section: Traditional Machine Learning As Feature Extractor and Deep Lmentioning
confidence: 99%
“…At the same time, since it is considered that the amount of data to be processed is large, it is necessary to select a muscle group that is as small as possible and has a substantial correlation. Through the search for a large number of related literatures [20]- [25] and experimental tests, it was found that the three muscle groups have a great correlation with the determined nine fine gestures: the abductor halluces muscle (APL), the superficial flexor (FDS), ulnar wrist flexor (FCU). After determining the location of the muscle group, place the three Music Muscle sensors in these three locations.…”
Section: B Electrode Positionmentioning
confidence: 99%
“…One of the branches is myography, which studies the electrical signal from the brain, whose responsibility is muscle control. The myoelectric wave (EMG) provides a load of information that is employed to perform a physical diagnosis and develop systems that permit the conception of intelligent prostheses [6]. This research addresses the problem of classifying movements according to the EMG.…”
Section: Introductionmentioning
confidence: 99%